A Mathematical Approach to Dampening Sea Waves Using Submerged Permeable Breakwater - Marpaung, J.L.; Tulus; Gultom, Parapat (Sinkron : jurnal dan penelitian teknik informatika, 2023)
A wave is an energy that can propagate with a medium; the propagation of a wave moves with respect to time by carrying energy that moves with velocity per unit of time. Sea waves are one of the propagating wave problems that are broken down to produce wave propagation with a relatively inhomogeneous minimum amplitude and speed of sea waves, which have their own difficulties in solving them numerically. This study aims to analyze the stability of wave propagation on submerged breakwaters. This research will approximate the finite discretization of the breakwater domain and then combine it with the Finite Element Method to determine the moving elements of the velocity of fluid flow through a porous submerged breakwater. The research has explained the equation of the inflated wave and the simulated representation displayed on the wave breakdown process, the point that becomes the center of the waves breakdown will give a focused red color indicator meaning there is a change in momentum and potential energy that occurs and then changes the colour of the post-flattering of the sea wave so that the sinking wave breaker is a method to obtain the minimum speed and amplitude values that can be used for coastal engineering.